2023
DOI: 10.1088/1758-5090/acc68f
|View full text |Cite
|
Sign up to set email alerts
|

Development of a biomimetic arch-like 3D bioprinted construct for cartilage regeneration using gelatin methacryloyl and silk fibroin-gelatin bioinks

Abstract: In recent years, engineering biomimetic cellular microenvironments have been a top priority for regenerative medicine. Collagen II, which is arranged in arches, forms the predominant fiber network in articular cartilage. Due to the shortage of suitable microfabrication techniques capable of producing 3D fibrous structures, in vitro replication of the arch-like cartilaginous tissue constitutes one of the major challenges. Hence, in the present study, we report a 3D bioprinting approach for fabricating arch-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…GeneMANIA software was used to predict the correlation and interaction of the input genes with the pool of genes associated with articular cartilage homeostasis. Through this analysis, we can validate the importance of the chosen set of genes for qPCR . Furthermore, all the experimental groups were chosen from one single donor showing maximum chondrogenic characteristics (donor-2) and the respective 5 upregulated genes of each experimental group were selected for the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GeneMANIA software was used to predict the correlation and interaction of the input genes with the pool of genes associated with articular cartilage homeostasis. Through this analysis, we can validate the importance of the chosen set of genes for qPCR . Furthermore, all the experimental groups were chosen from one single donor showing maximum chondrogenic characteristics (donor-2) and the respective 5 upregulated genes of each experimental group were selected for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Through this analysis, we can validate the importance of the chosen set of genes for qPCR. 58 Furthermore, all the experimental groups were chosen from one single donor showing maximum chondrogenic characteristics (donor-2) and the respective 5 upregulated genes of each experimental group were selected for the analysis. The different colors represent the different forms of interactions between the respective genes.…”
Section: Protein Expression Analysismentioning
confidence: 99%
“…In another study, the uniaxial arrangement of myoblasts in gelatin methacryloyl (GelMA) was accomplished by the in-situ crosslinking process during 3D bioprinting [39] . The related in vitro and in vivo experiments found that GelMA scaffolds loaded with cells with arranged cell structures are expected to become a promising platform for promoting muscle regeneration.…”
Section: Bioprintingmentioning
confidence: 99%
“…Gelatin methacryloyl (GelMA) is a commonly used hydrogel that exhibits excellent biocompatibility and can be easily functionalized to incorporate bioactive cues 4 , 7 , 8 . GelMA-based hydrogels have shown great potential for cartilage tissue engineering applications such as drug screening 9 11 . They provide a compatible and scaleable microenvironment for enhanced chondrogenic cell viability and functionality 12 .…”
Section: Introductionmentioning
confidence: 99%